Beyond Stewardship: Toward a Batak Toba Eco-Theology of Friendship and Relational Ontology - Roy Charly HP Sipahutar; Welko Henro Marpaung; Fredy Simanjuntak (Institut Kristen Teologi Real Batam, 2026)
The ecological crisis in the Batak lands, manifested in flooding, landslides, pollution of Lake Toba, and forest degradation, reflects a crisis of relationship between humanity, nature, and God rooted in an anthropocentric paradigm. Although global ecotheology has critiqued this paradigm through the concept of stewardship, such an approach is considered to retain hierarchical relational structures. This article aims to formulate a Batak Toba ecotheology of friendship as a post-stewardship relational ontology by positioning local cosmology as a locus theologicus. This study employs a qualitative-theological approach using Stephen B. Bevans’s anthropological model of contextual theology, based on a literature review and critical analysis of the dialogue between the ecological crisis, Batak Toba cosmology, and Christian theological reflection. The findings indicate that the human-nature relationship in Batak Toba cosmology is genealogical and communal, whereby ecological responsibility is understood as fidelity to cosmic kinship. This paradigm offers a transformative spiritual-ethical framework for the church in responding to ecological crises in a contextual and sustainable manner. Abstrak Krisis ekologis di Tanah Batak, yang tampak dalam banjir, longsor, pencemaran Danau Toba, dan degradasi hutan, mencerminkan krisis relasi antara manusia, alam, dan Allah yang berakar pada paradigma antroposentris. Meskipun ekoteologi global telah mengkritiknya melalui konsep stewardship, pendekatan ini dinilai masih menyisakan struktur relasional yang hierarkis. Artikel ini bertujuan merumuskan ekoteologi persahabatan Batak Toba sebagai ontologi relasional pasca-stewardship dengan menjadikan kosmologi lokal sebagai locus theologicus. Penelitian menggunakan pendekatan kualitatif-teologis melalui metode teologi kontekstual model Antropologi Stephen B. Bevans, berbasis studi pustaka dan analisis kritis atas dialog antara krisis ekologis, kosmologi Batak Toba, dan refleksi teologis Kristen. Melalui dekonstruksi teks-teks kultural, kajian ini mengonstruksi ulang relasi manusia-alam dalam kosmologi Batak Toba yang bersifat genealogis dan komunal menjadi sebuah etika kesetiaan kosmik. Kebaruan yang ditemukan adalah konseptualisasi hubungan non-hierarkis di mana alam bertindak sebagai subjek mitra, yang menawarkan kerangka spiritual-etis bagi gereja dalam merespons krisis ekologis secara kontekstual dan berkelanjutan.